Sustainable consumption in the circular economy. An analysis of consumers' purchase intentions for waste-to-value food. (10th April 2020) - Coderoni, Silvia; Perito, Maria Angela
Abstract: This study is aimed at evaluating the relative influence of socio-demographic and psychological features that rule the extent to which consumers engage in the circular economy, purchasing waste-to-value (WTV) food enriched with ingredients otherwise wasted in the supply chain. 477 Italian consumers replied to a web-based questionnaire administered through different social media networks. Two different consumers' purchase intentions were analysed: consumers were asked both if they would be willing to buy WTV food and if they would buy WTV food if this would help to reduce the environmental impact of agricultural production. Binary logistic regressions are estimated to appraise the eventual drivers of consumers' statements. Among these drivers, attention was given to aspects related to the generalised aversion to new foods, i.e. food neophobia (FN) and the aversion to food processed in new ways, i.e. food technology neophobia (FTN). Other relevant economic and demographic factors were investigated, together with aspects related to generalised trust, purchase behaviours and preferences. The main results indicate that 56% of respondents declared to be willing to buy WTV food, however, FN and FTN negatively influence the probability of stating a positive purchase intention. Consumers who give importance to reading food labels and think that food could have environmental or health benefits, are more likely to be willing to buy WTV food. In addition, a core of sustainable consumers seems to emerge who express a positive purchase intention for WTV food to reduce the environmental impact of production and give importance to the origin and nutritional values of products. In conclusion, policy implications are drawn. Highlights: Consumers' acceptance for food derived from food by-products was evaluated. A web-questionnaire was administered to a sample of Italian consumers. The influence of food neophobia, food technology neophobia was investigated. Positive purchase intentions for a core of sustainable consumers were found.